Trends in the Physical Medicine and Rehabilitation Match: Analysis of NRMP Data from 2007 to 2018. Issue 9 (18th January 2021) - Claus, Deanna; Anderson, Dustin; Staley, Vera; Forster, Jeri; Meron, Adele
Abstract: Introduction: We provide an updated analysis of data about U.S. Physical Medicine and Rehabilitation (PM&R) residency program applicants collected by the National Resident Matching Program (NRMP). Objective: Analyze trends within NRMP data for PM&R residency match rates, compare matched to unmatched applicants, and compare PM&R applicants to other medical specialties. Design: Secondary analysis of NRMP data. Setting: NRMP data set. Participants: Residency program applicants who participated in the NRMP Match, 2007 to 2018. Interventions: Not applicable. Main Outcome Measures: Number of applicants, match rates, difference in characteristics including rank order list (ROL), U.S. Medical Licensing Examination (USMLE) Step 1 and Step 2 Clinical Knowledge (CK) scores, publications, Alpha Omega Alpha (AOA) status, PhD degree, and experiences in research, volunteer, and work. Results: Number of applicants and residency positions increased from 2007 to 2018. Length of ROL increased and was longer for matched compared to unmatched applicants, with maximum mean difference of 7.4 in 2016 (95% confidence interval [CI] 5.6‐9.2). Matched U.S. Allopathic Seniors had higher USMLE scores compared to unmatched, with a mean difference of 12.7 for Step 1 (95% CI 8.3‐17.0) and 12.6 (95% CI 8.6‐16.6) for Step 2 CK ( P < .001). Number of publications and volunteer experiences were higher for matched U.S. Allopathic Seniors (0.64, 95% CI 0.09‐1.2 and 1.5, 95% CI 0.65‐2.3, respectively). PM&R USMLE Step 1 and 2 CK scores increased at a significantly faster rate than for all other specialties, with estimated rate differences of 0.46 (95% CI 0.21‐0.71) and 0.69 (95% CI 0.45‐0.93) points per year, respectively. Conclusions: PM&R residency has become more competitive. USMLE Step 1 and 2 CK scores have outpaced the inflation of scores in other specialties. ROL length has increased, suggesting more ranked programs to successfully match. These analyses update our knowledge about PM&R residency applicants and suggest surrogate markers for a successful match.